(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
This article examines the specifics of the information landscape of compensation systems in the context of using an integrated information-analytical resource management solution (based on the functionality of the "Galaktika ERP" software suite). The focus of the research is on the features of informational support for procedures related to payroll organization. Emphasis is placed on the interaction between individual ERP-system components during the formation of data arrays necessary for accurate calculations; a model of such informational interaction is presented based on identified information flows circulating within the accounting-analytical system. In preparing the article, general scientific methods (analysis and synthesis) were used, along with methods for studying the regulatory and legal framework and the scientific-methodological discourse related to the topic, as well as modeling techniques. The analysis revealed problematic aspects in the accounting support of personnel calculations and provided considerations regarding directions for further scientific development of this issue.